2004
DOI: 10.1016/j.bbamem.2004.05.008
|View full text |Cite
|
Sign up to set email alerts
|

l-Leucine transport in human breast cancer cells (MCF-7 and MDA-MB-231): kinetics, regulation by estrogen and molecular identity of the transporter

Abstract: The transport of L-leucine by two human breast cancer cell lines has been examined. L-leucine uptake by MDA-MB-231 and MCF-7 cells was via a BCH-sensitive, Na+ -independent pathway. L-leucine uptake by both cell lines was inhibited by L-alanine, D-leucine and to a lesser extent by L-lysine but not by L-proline. Estrogen (17beta-estradiol) stimulated L-leucine uptake by MCF-7 but not by MDA-MB-231 cells. L-leucine efflux from MDA-MB-231 and MCF-7 cells was trans-stimulated by BCH in a dose-dependent fashion. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 30 publications
6
51
0
Order By: Relevance
“…This differential regulation between liver and breast may be due to numerous tissue-specific differences, including coactivator/corepressor balance or availability. Given the key role of FXR in regulating the expression of transporters in the liver and the restricted high-level expression of FXR in normal ductal epithelial cells, the effects of FXR ligand on the expression of other transporters, known to be expressed in breast, were examined (37,47). Both MRP1 and SLC7A5 were down-regulated by FXR ligand in MCF-7 cells.…”
Section: Discussionmentioning
confidence: 99%
“…This differential regulation between liver and breast may be due to numerous tissue-specific differences, including coactivator/corepressor balance or availability. Given the key role of FXR in regulating the expression of transporters in the liver and the restricted high-level expression of FXR in normal ductal epithelial cells, the effects of FXR ligand on the expression of other transporters, known to be expressed in breast, were examined (37,47). Both MRP1 and SLC7A5 were down-regulated by FXR ligand in MCF-7 cells.…”
Section: Discussionmentioning
confidence: 99%
“…They also studied the protein expression of LAT1 and 4F2hc in T24 cells. 18,19) Shennan et al 27) reported the Na ϩ -independent BCH-sensitive L-leucine transport activity and expression of LAT1 mRNA in human breast cancer cells, MCF-7 and MDA-MB-231. Here, we studied to compare the expression levels of LAT1 and 4F2hc mRNAs and the proteins in several human tumor cell lines including gastrointestinal epithelial cell lines, with those in HeLa and T24 cells by real-time quantitative PCR and Western blotting, respectively.…”
Section: The Expression Of Lat1 and 4f2hc In Human Tumormentioning
confidence: 99%
“…Actively proliferating cancer cells require more nutrients, such as amino acids and glucose, than quiescent cells. With regard to the relationship between LAT1 and breast cancer, there have been only four publications so far reporting the role of LAT1 in two cultured breast cancer cell lines, from Shennan and his colleagues [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%